UJI ANTIOKSIDAN DARI FORMULASI SEDIAAN FACE MIST EKSTRAK DAUN JAMBU AIR (Syzygium samarangense) - Katharina Anrina; Gigih Kenanga Sari; Maulita Saraswati (Joseph: Journal of Science and Pharmacy, 2023)
Background :Antioxidants are compounds that can neutralize free radicals. One of the most frequently used antioxidant cosmetic preparations is face mist. Purpose : To make face mist preparations of water guava leaf extract (Syzygium samarangense) with good physical quality and IC50 value. Method : Water guava leaf extract (Syzygium samarangense) was macerated with 70% ethanol solvent and tested for water content, drying shrinkage, ethanol free, and chemical compound content. Next, evaluation of the preparation was carried out and antioxidant test were carried out on the face mist of water guava leaves (Syzygium samarangense) with concentrations of extract FI 3 grams, FII 5 grams, and FIII 7 grams using the UV-VIS spectrophotometric DPPH (1,1-diphenyl-2-picrylhydrazyl) method at wavelength of 517 nm with ratio of vitamin C. Result : This research shows that water guava leaf extract (Syzygium samarangense) can be used as a good face mist preparation and contains flavonoids, saponin, tannin, and triterpenoid which act as antioxidant. On the face mist preparation of guava leaf extract (Syzygium samarangense) produced good physical quality and the IC50 value at FI was 24,54 ppm, FII was 17,61 ppm, and FIII was 8,86 ppm, so that face mist preparation had the best antioxidant content is an FIII preparation with an IC50 value of 8,86 ppm. Conclusion : Water guava leaf extract (Syzygium samarangense) can be made into a face mist with good physical quality and produces the best antioxidant antivity in FIII preparations with an IC50 value of 8,86 ppm